TUJUAN PENDIDIKAN PERSPEKTIF Al-QUR’AN DAN AL-HADIST - Faiqotul Hikmah; Imam Ghozali; Inarotul Chasanah; Muhammad Hori (As-Sulthan Journal of Education, 2026)
This study explores the goals of education from the perspective of the Qur’an and Hadith, emphasizing the theological foundations, value concepts, and their relevance to the needs of Islamic education in the modern era. The research highlights that education in Islam is not merely focused on the acquisition of knowledge but also on character formation, intellectual development, and the strengthening of faith and piety toward Allah SWT. The Qur’an, through verses such as Al-‘Alaq: 1–5 and Adz-Dzariyat: 56, provides a philosophical framework that views education as an integral process combining spirituality and rationality. Meanwhile, the Hadith reinforces that knowledge must lead to humility and goodness that benefits humanity. The findings indicate that the objectives of Islamic education encompass four core aspects: aqidah (faith), ibadah (worship), akhlak (morality), and muamalah (social relations). These four dimensions serve as the foundation for forming Islamic character capable of adapting to global challenges without losing spiritual values. Therefore, Islamic education remains relevant and essential in building a civilized society in the midst of the digital era’s dynamics.